Moral Messages & Action Film (Semiotic Analysis Roland Barthes In The Film Bad Boys For Life) - Ichsan Adil Prayogi; Annisarizki; Ahmad Maulana Harahap (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to analyze the meaning of Roland Barthes' Semiotics which include denotative, connotative, and mythical meanings. The film is directed by Bilall Fallah and Adil El Arbi and starred Will Smith and Martin Lawrence in the film Bad Boys for Life. This study used the descriptive qualitative method. The object of this research is several scenes in the film Bad Boys For Life. The results of this study found that in the film Bad Boys For Life, several scenes or scenes contain moral messages. Some of the moral messages that are divided through the scenes that the researcher chooses include; First, the law of karma that applies and the consequences of every action taken. The second moral message is how the family can be the main factor in shaping a child's personality, therefore parents must reflect something good in front of their children so that they become good children and are useful to their environment. Third, the doctrine that is carried out by parents can affect the condition of the child, the existence of fear, and the taking of the child's right to speak, the taking of the child's right to express his opinion because it is fixed by the doctrine expected by the parents.